2017
DOI: 10.1016/j.bbamcr.2017.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone/bicalutamide antagonism at the predicted extracellular androgen binding site of ZIP9

Abstract: ZIP9 is a Zn transporter, testosterone receptor, and mediator of signaling events through G-proteins. Despite these pivotal properties, however, its physiological and pathophysiological significance has not yet been comprehensively addressed. Using a cell line that lacks the classical androgen receptor we show that ZIP9-mediated phosphorylation of Erk1/2, CREB, or ATF-1 and expression of claudin-5 and zonula occludens-1 by testosterone can be completely antagonized by bicalutamide (Casodex), an anti-androgen o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 64 publications
4
24
0
Order By: Relevance
“…HF is an active metabolite of pure AR antagonist, flutamide, which does not block membraneinitiated androgen actions [12,[37][38][39]. In contrast, Bic was demonstrated to inhibit activation of both AR and ZIP9 [40,41].…”
Section: Resultsmentioning
confidence: 99%
“…HF is an active metabolite of pure AR antagonist, flutamide, which does not block membraneinitiated androgen actions [12,[37][38][39]. In contrast, Bic was demonstrated to inhibit activation of both AR and ZIP9 [40,41].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, as evidenced by studies on Sertoli cell‐specific AR knockout (SCARKO) mice the expression of claudin‐11, another TJ protein important for BTB integrity, is regulated by testosterone action through the AR (Tan et al ., ; Willems et al ., ). In agreement with previous in vitro findings from rat and mouse Sertoli cells (Kaitu'u‐Lino et al ., ; Bulldan et al ., ), in TM4 cells we observed upregulation of both claudin‐11 and claudin‐5 mRNA and protein following testosterone treatment.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, to explore the interplay between androgen-regulated cellular functions and Notch signaling, we investigated the expression of claudin-5 and claudin-11 after DAPT treatment and RBP-J silencing. Recently, Bulldan et al (2017) demonstrated that blockade of ZIP9 receptor in AR-deficient rat Sertoli cells resulted in decreased claudin-5 and ZO-1 and disturbed tight junction (TJ) formation between the cells, indicating a role of ZIP9 in BTB function. On the other hand, as evidenced by studies on Sertoli cell-specific AR knockout (SCARKO) mice the expression of claudin-11, another TJ protein important for BTB integrity, is regulated by testosterone action through the AR (Tan et al, 2005;Willems et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that HT develops following castration of the androgen receptor-deficient Tfm rats provides strong evidence that the anti-hypertensive effects of TES on the vasculature and kidney rely upon nongenomic mechanism(s) independent of the classic cytosolic AR that mediates the genomic effects of this hormone. In reproductive tissue cultures, AR-independent actions of TES are mediated by membrane receptors that can bind TES, such as the ZIP9 Zinc transporter [59] or other membrane-associated androgen receptor proteins [60]. These receptors appear to mediate the effects of TES via rapid activation of ERK1/2, Akt, and CREB signaling cascades.…”
Section: Mechanisms Underlying Anti-hypertensive Effects Of Androgensmentioning
confidence: 99%